Therapeutic radiographers supporting individuals undergoing radiotherapy to stop smoking: Testing a training resource in clinical practice. (October 2021) - Charlesworth, L.; Hutton, D.; Hussain, H.; Wong, H.
Abstract: Introduction: This study developed and piloted the first online training package to support implementation and delivery of brief smoking cessation interventions for therapeutic radiographers in four radiotherapy departments in England. Methods: A previously reported systematic literature review and data analysis from the previously reported pre-focus group questionnaire and focus groups enabled the development of an online training package. The questionnaire was repeated by the participating therapeutic radiographers following completion of the training resource (n = 31). The results of the comparative questions from the pre and post questionnaires were analysed using the Statistical Package for Social Sciences (SPSS Version 24). Results: In total, 43 therapeutic radiographer participants completed the pre-questionnaire and 31 participants continued to complete the post questionnaire, having completed the online training package. The previously conducted focus groups identified several barriers to the delivery of smoking cessation, that were addressed through the development of an online training package. Following the completion of the training; therapeutic radiographers had increased knowledge and confidence regarding smoking cessation, the number of therapeutic radiographers who believe that smoking cessation is part of their role increased and therapeutic radiographers more routinely have conversations about smoking cessation. Conclusion: The training resource improved therapeutic radiographers' knowledge and confidence and increased awareness of the role of the therapeutic radiographer in the provision of smoking cessation interventions. Challenges remain that continue to prevent some therapeutic radiographers from delivering smoking cessation interventions and strong leadership and implementation of strategy and guidance is essential to ensure wider implementation. Recording and measuring impact of interventions remains an area to be addressed, alongside cultural changes and reassurance around the therapeutic relationship. Implications for practice: This training tool has proven to be effective in the sample within this study and should be disseminated and evaluated more widely across radiotherapy provision within the United Kingdom.